An in vivo comparison of accuracy of two electronic apex locators in determining working length using stainless steel and nickel titanium files - Chaudhary S; Gharti A; Adhikari B (Dove Medical Press, 2018)
Sanjeeb Chaudhary, Archana Gharti, Bhawana Adhikari Department of Conservative Dentistry and Endodontics, School of Dental Sciences, Chitwan Medical College, Bharatpur, Nepal Purpose: A key factor affecting the success of endodontic treatment is correct determination of root canal working length (WL). The purpose of this in vivo study was to compare the accuracy of Propex II and iPex II electronic apex locator (EAL) in determining the WL under clinical conditions, to that of radiographic working length (RWL) using stainless steel (SS) and nickel–titanium (NiTi) hand files. Patients and methods: Thirty-seven patients, with 60 anterior teeth (60 canals) scheduled for endodontic treatment participated in this study after ethical approval. Electronic working length (EWL) was determined by the Propex II and iPex II according to manufacturer’s instructions using SS Hand K-files and NiTi Hand files. RWL was determined after EWL determination. The results obtained with each EAL with SS and NiTi files were compared with RWL. Data was analyzed statistically at a significance level of p < 0.05. Interclass correlation coefficient was calculated. Results: Statistical analysis revealed no significant difference between the EALs, indicating similar accuracies between them with respect to accuracy in determining the WL (p > 0.05). No significant difference was found between the EWL and RWL and between SS and NiTi files for WL determination (p > 0.05) as well. The result also displayed a high intraclass correlation coefficient between the RWL and EWL measurement methods. Conclusion: Under the in vivo clinical conditions of this study, both Propex II and iPex II were similar to the RWL determination technique showing high correlation to RWL. Both are clinically acceptable EAL for WL determination and both SS hand K-file and NiTi file can be used interchangeably without compromising the WL during treatment. Keywords: working length determination, minor diameter, electronic apex locator, electronic working length, radiographic working length